Perbandingan Perilaku Akibat Pembebanan Pada Konstruksi Sistem Rangka dan Konstruksi Sistem Ganda - Dharma, I Made Sotya Wira; Sinarta, I Nengah; Aryastana, Putu (Fakultas Teknik, Universitas Wiraraja, 2025)
As the height of a building structure increases, the building becomes more vulnerable to responding to lateral loads, which is why a dual-system approach is used to resist the lateral forces that occur in the structure. The use of moment-resisting frame systems (MRF) and dual systems differs particularly in terms of earthquake loads. Based on these conditions, an analysis was performed to compare the effects of loading on a frame system versus a dual system in the structural design of the RSU BaliMed Negara building. In the modeling process, two models were created: Structure 1 represents the existing condition, and Structure 2 incorporates the addition of shear walls. The analysis results show that the 100% mass participation value for Structure 1 is achieved at mode 34, whereas for Structure 2, it decreases to mode 15. The natural period of vibration is also influenced by the structural loading, with the addition of shear walls resulting in a shorter natural vibration period for Structure 2 compared to Structure 1. The base shear forces for Structure 1 are Vd in the X and Y directions at 4,856.70 and 4,856.41, respectively, and Vs in the X and Y directions at 4,635.12. For Structure 2, the values are Vd in the X and Y directions at 4,745.47 and 5,745.43, and Vs in the X and Y directions at 5,508.07. The displacement values for Structures 1 and 2 indicate that the displacement in Structure 2 is smaller.